TCI의 기질 및 성격 유형과 MMPI-2-RF 성격병리의 관계 - 김동주; 김은경; 박용천; Kim, Dongju; Kim, Eunkyeong; Park, Yong Chon (Anxiety and mood, 2021)
Objective : The purpose of the study was to investigate the relationship between temperament and character inventory (TCI) temperament, characteristics, and personality psychopathology in the Minnesota Multiphasic Personality Inventory-2-Restructured Form (MMPI-2-RF) in psychiatric patients. Methods : The TCI and MMPI-2-RF data of 240 psychiatric patients were used in this study. The data were classified according to the aspects of vulnerable temperament and immature character into four groups. Multivariate analysis of variance (MANOVA) was performed to investigate the TCI and MMPI-2-RF scores between the four groups. Results : All five personality psychopathologies were significantly different between the four groups. However, the diagnosis rate of multiple mental disorders was not significantly different between the four groups. Conclusion : The findings suggest that acquired personality traits play an important role in the adaptation of the individual, and personality pathological factors appear differently according to temperament and character types.